Desempenho produtivo do milho em função dos atributos químicos do solo, tendo em vista a intensificação ecológica - VALE, Clemeson Cardoso (2014)
The constant concerns over the unsustainable use of natural resources, coupled with rapid population growth, direct them to the productive process of maximizing resources systems to provide greater increases in production to minimize impacts to the environment yields. The objective of this research was to evaluate the performance of maize in no-tillage in legume straw depending on the spatial variability of soil chemical properties and nutrient input in a Dystrophic cohesive oxisol. The experiment was conducted in a 0.6 ha area containing two environments (without legumes and pulses) and 170 sampling points regularly dispersed (7.0 x 5.0 m) for chemical soil variability and productive maize yields. Data were initially analyzed using descriptive statistics and later by geostatistical methods. The interaction between soil chemical properties and yield of corn production was assessed by Pearson correlation to 5%. There was an increase in levels of soil chemical properties in the area with legumes compared to the area without legumes, proving the applicability of this management system to improve the chemical quality of the soil due to continuous addition of plant residues. Found the presence of spatial variability for all soil chemical properties and productive yield with spatial dependence ranged from moderate to strong, allowing reveal through thematic maps the potentialities and limitations of the production system. The productive efficiency, productivity specifically, correlated positively with calcium, sum of bases, phosphorus, potassium, base saturation and cation exchange capacity.